Healthy Living: Diabetes Care During Sick Days - Jennifer Hillan (EDIS)
FCS8819, a 3-page fact sheet by Jennifer Hillan, will help people with diabetes plan and manage their care on days when they are ill. Includes information on how illness can affect blood glucose, suggestions for easy foods to have on hand, and a checklist to use when deciding whether a call to a doctor is in order. Published by the UF Department of Family, Youth and Community Sciences, December 2006.